Digital media as ambient therapy : the ecological self between resonance and alienation - Russell, Francis (Researcher) (Abingdon, Oxon ; New York, NY : Routledge, 2024)
"Digital Media as Ambient Therapy explores the ways mental illness can emerge from our relationships (with ourselves, others, and the world), to address the concern around what kind of relationality is conducive for mental health and what role digital technologies can play in fostering such relationality. Exploring the rise of ambient-that is to say, ubiquitous, surrounding, and environmental-technologies and their impact on our understanding of health, sanity, and therapy, this book critically examines the work of influential contemporary social theorists such as Hartmut Rosa, and investigates case studies that reveal new modes of digitally mediated intimacy and attention, such as ASMR and QAnon. It also poses the question of what "mental health" and "mental illness" mean for subjects increasingly faced with a maddening sense of interconnectedness. This book offers new perspectives for cultural studies academics and postgraduates interested in critical discussions of alienation, digital technology, and contemporary social theory"--
From "mental illness" to "environmental illness" -- Mute instruments and resonant relations -- The agonies of freedom and control -- QAnon : from the resonant to the digitally sublime.
Keywords: Mental illness in mass media; Digital media -- Social aspects; Digital media -- Psychological aspects; Alienation (Social psychology); SOCIAL SCIENCE / Handicapped; MEDICAL / Mental Health